Strengthening China's Environmental Protection Administrative System : Analysis and Recommendations - World Bank (2013)
The Chinese economy has experienced an unprecedented 30-year period of economic growth and development that has delivered enormous social and economic benefits to the people but has had seriously adverse and continuing effects on the state of the environment. The government is well aware of the problem. Over the last five to ten years, environmental objectives have become increasingly important in priorities set under successive national five-year plans. To address these problems, the government has provided increasingly large infusions of capital and implemented a series of administrative reforms. Notwithstanding all these actions, the state of the national environment continues to deteriorate, and further action is clearly needed. This policy note focuses particularly on continuing issues related to the operations of the Ministry for Environmental Protection (MEP), including the legal framework under which it operates and its operational relationships with other agencies at the national level and with its counterparts at lower levels of government. This focus is justified given that MEP's effectiveness is critical to the effectiveness of the government's overall environmental objectives. Without an effective MEP, the other elements necessary for China's environmentally sustainable development will not be able to achieve these national goals.